Ekspresi Verbal dan Nonverbal Customer CGV Cinemas Focal Point Medan terhadap Carry Bullying pada Instagram - Ruslan Hakiki Sambo; Effiati Juliana Hasibuan; Taufik Wal Hidayat (Universitas Medan Area, 2019)
Oppression is a violence, threat or force to abuse or intimidate others, bullying on social media has become entertainment through memes, in giving opinion research and perception of memes on Instagram. This research concerning the corruption case of the former chairman of thePartai Golongan Karya Setya Novanto, has caused so many memes that satirize the official. This type of research is qualitative, with a descriptive approach. The source of this research data obtained through primary data and secondary data, from the theories of verbal and nonverbal communication can provide carry media social media data especially on instagram, this research was conducted to find out the perception of social media users especially on instagram.